Analysis of Half Round Runner Dimensions Influence to Plastics Injection Results on Making Door Handle Using Taguchi Method - Ulfa Fairuz Izdihar; Jata Budiman; Gamawan Ananto (Institut Teknologi Sepuluh Nopember, 2019)
Runner is a part of channel systems that flows the molten plastics from the sprue to the gate with a specified layout. The selection of runner shapes are according to the design of the mold and the product. Usually, the diameter of half round runner is calculated by the existing empirical formula. Predictably, the dimension of the runner is one of the factors that will be influencing the injection process and the resulting product. The objectives of experiment are to know how big the runner diameter that will be influencing the taken response and to prove that the existing empirical formula for calculating the diameter of runner is efficient. The experiment is designed by Taguchi method using Minitab applications to generate data of the influences of the runner diameter. The responses of this experiment are cycle time and product mass. The experiment is conducted by using the door handle products with Acrylonitrile-butadiene-styrene as known as ABS material. Besides diameter of runner, there are also other factors from parameters of injection process to be considered, they are nozzle temperature and injection pressure. In reference to Taguchi method, the authors took nine times experiment with three replications or repetitions for each data of experiment. The data from experiment were analyzed and calculated by Analysis of Variance (ANOVA) using Minitab applications to generate the results of experiment. As a result, the diameter of the runner had impact on the responses taken, either to cycle time and product mass as well. In conclusion, the runner diameter was ranked as the most influential compared to nozzle temperature and injection pressure